As práticas sociais do binômio cuidador familiar/equipe de saúde em um serviço de assistência domiciliar - Borges, Marianne Viana (2013)
Knowledge as a resource in the interorganizational relationships is growing in the international and national literature. The current study aims to analyze the interorganizational knowledge sharing between Petrobras UN-ES and the NGOs and Petrobras UN-ES